Fostering Creativity in Multiple Intelligences: Philosophizing at School in the Atelier - Eleonora Zorzi; Sofia Marina Antoniello (Encyclopaideia, 2020)
A research-action path carried out in the second class of primary school is presented, to encourage the promotion of creativity declined in the different ways of thinking that are described within the theoretical framework of multiple intelligences. The hypothesis from which the research-action work starts is that creativity, in its plural forms, can promote a school of each and everyone, and for this reason, the Italian school must recognize it (again) space and dignity. Promoting creativity also becomes a cultural choice, for a society that returns to reflect on the ethical meaning of education.